The relationship between workload and performance of research university academics in Malaysia: the mediating effects of career commitment and job satisfaction - Janib, Jamali; Mohd Rasdi, Roziah; Omar, Zoharah; Alias, Siti Noormi; Zaremohzzabieh, Zeinab; Ahrari, Seyedali (Faculty of Education, Universiti Teknologi Mara, 2021)
The purpose of this study is to test the relationship between job workload and academic performance among university academic staff in Malaysia. The paper also attempts to discuss and then seek empirical evidence to the two mediational paths (namely, career commitment and job satisfaction) that explain the focal relationship between job workload and academic performance. To test the three proposed hypotheses, the study used cross-sectional data collected from academic staff serving in Malaysian Research Universities (MRUs). The final sample of 191 valid and complete responses was analysed using SmartPLS 3.3.3 to test the hypotheses. Results showed that workload is negatively related to academic staff performance. In addition, job satisfaction mediates workload and academic staff performance linkage. These findings reinforce the importance of job satisfaction as an influencing factor against the deleterious effect of job workload and academic staff performance. The study has shown that, contrary to our expectations, career commitment does not mediate the relation between job workload and academic staff performance. Going forward, this study provides new insights about the effect of job workload on the performance of university academic staff through intervening variables.